Study and Implemenation of Solar Botics - Nidhi, R (International Journal of Computer Sciences and Engineering, 2025)
The battery life of robots is increasing by harvesting energy from the environment with photovoltaic solar panels. Solar harvesting has proven to be useful in marine and extra-terrestrial robotics applications which take place in open space. This is a far more cost effective solution than purchasing additional solar panels. It has been estimated that the yield from solar panels can be increased by 30 to 60 percent by utilizing a tracking system instead of a stationary array. The system implemented in paper develops an automatic tracking system which will keep the solar panels aligned with the sun in order to maximize efficiency, then after one can add a battery which can be charged through solar panels. The battery is finally connected to a robot which performs the desired activity.